2017
DOI: 10.6063/motricidade.9746
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Basic Psychological Needs in Subjective Happiness, Subjective Vitality and Physical Activity in an Elderly Portuguese Population

Abstract: The goal of this work is to analyze the impact of elderly Portuguese individuals' global perception of satisfying basic psychological needs in the areas of subjective happiness, subjective vitality and physical activity through a structural equations model. The way of well-being differs according to the amount of physical activity practiced in Portuguese elderly was also analyzed. Participants included 309 elderly people (242 females, 67 males) of Portuguese nationality who practice different levels of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
1
10
0
1
Order By: Relevance
“…Considering previous research, we hypothesised that relatively more-active (higher exercise frequency) versus less-active (lower exercise frequency) exercisers will experience more positive affect (Magnan et al, 2013). In turn, we also speculate that positive affect would have a positive relationship with life satisfaction, self-esteem, and vitality (Couto et al, 2017;Ryan & Deci, 2017). On the other hand, higher engagement in regular physical activity would have a negative relationship with negative affect (Niermann et al, 2016), which ultimately is negatively associated with previously reported outcomes (Ryan & Deci, 2017;Ye & Lin, 2015).…”
Section: Current Researchmentioning
confidence: 84%
See 1 more Smart Citation
“…Considering previous research, we hypothesised that relatively more-active (higher exercise frequency) versus less-active (lower exercise frequency) exercisers will experience more positive affect (Magnan et al, 2013). In turn, we also speculate that positive affect would have a positive relationship with life satisfaction, self-esteem, and vitality (Couto et al, 2017;Ryan & Deci, 2017). On the other hand, higher engagement in regular physical activity would have a negative relationship with negative affect (Niermann et al, 2016), which ultimately is negatively associated with previously reported outcomes (Ryan & Deci, 2017;Ye & Lin, 2015).…”
Section: Current Researchmentioning
confidence: 84%
“…Much of the impetus for examining the correlates of positive/negative affect comes from the association of positive wellbeing with health, and the research literature showing that psychological well-being is related to better health is growing (Ekkekakis et al, 2020). There is evidence that positive affect is associated with greater experience of subjective vitality (Couto et al, 2017). Contrarily, negative affect might reflect pessimism or doubts that efforts to improve one's health will provide adaptive outcomes.…”
Section: Correlates Of Positive and Negative Affects: Self-esteem Life Satisfaction And Vitalitymentioning
confidence: 99%
“…However, it was verified that the BPN of competence and autonomy were those that demonstrated a higher effect on the studied well-being variables. Couto et al (2017) also verified that competence is the BPN that performance the highest effect on elderly subjective well-being, by the influence of this need on happiness. The need of competence (i.e., the subject ability of be effective in the interaction with the enveloping) has a central role for the subjective wellbeing in this population, once, according to Neto, Lima, Gomes, Santos, and Tolentino (2012), is understood as the capacity that the subject has in resorting to compensatory activities.…”
Section: Discussionmentioning
confidence: 57%
“…The present study was carried out with the objective of analyzing the associations between motives for physical exercise, positive and negative activations, and self-esteem of Portuguese women exercising at gyms and fitness centers. Based on past research, we hypothesized that intrinsic motives would be positively and significantly associated with positive activations and self-esteem [ 9 , 12 , 46 ]. We also hypothesized that extrinsic motives would be negatively and significantly associated with positive activations and self-esteem [ 9 , 12 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on past research, we hypothesized that intrinsic motives would be positively and significantly associated with positive activations and self-esteem [ 9 , 12 , 46 ]. We also hypothesized that extrinsic motives would be negatively and significantly associated with positive activations and self-esteem [ 9 , 12 , 46 ]. Looking at exercise motives, we speculate that intrinsic motives would have the most significant associations with self-esteem compared to extrinsic motives [ 9 , 12 , 46 ].…”
Section: Introductionmentioning
confidence: 99%